2023
DOI: 10.3389/fpls.2023.1197706
|View full text |Cite
|
Sign up to set email alerts
|

Race-specific genotypes of Pseudomonas syringae pv. tomato are defined by the presence of mobile DNA elements within the genome

Abstract: Pseudomonas syringae pv. tomato is the causal agent of bacterial speck of tomato, an important disease that results in severe crop production losses worldwide. Currently, two races within phylogroup 01a (PG01a) are described for this pathogen. Race 0 strains have avirulence genes for the expression of type III system-associated effectors AvrPto1 and AvrPtoB, that are recognized and targeted by the effector-triggered immunity in tomato cultivars having the pto race-specific resistance gene. Race 1 strains inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Through a transcriptomic approach carried out on the P. syringae pv. tomato strain used in the study of Orfei et al ( 2023a ), whose genome we recently sequenced (Orfei et al 2023b ) to better perform the transcriptomic analysis, we demonstrated that the exposition of bacterial cells for 10 and 30 min at sub-letal doses of Argirium - SUNCs induced change in the expression of genes associated with transporters ( e . g ., CadA P-type ATPase, the arsenite resistance efflux pump, multidrug resistance proteins), iron homeostasis ( e .…”
Section: Silver Ultra Nano Clusters ( Argirium - ...mentioning
confidence: 73%
“…Through a transcriptomic approach carried out on the P. syringae pv. tomato strain used in the study of Orfei et al ( 2023a ), whose genome we recently sequenced (Orfei et al 2023b ) to better perform the transcriptomic analysis, we demonstrated that the exposition of bacterial cells for 10 and 30 min at sub-letal doses of Argirium - SUNCs induced change in the expression of genes associated with transporters ( e . g ., CadA P-type ATPase, the arsenite resistance efflux pump, multidrug resistance proteins), iron homeostasis ( e .…”
Section: Silver Ultra Nano Clusters ( Argirium - ...mentioning
confidence: 73%
“…Typical symptoms of the bacterial speck consist in small and dark lesions on leaves, usually surrounded by a yellow halo, and necrotic spots along stems and on fruits, provoked by a coronatine toxin; from necrotic lesions the germs can evade the plant as bacterial exudates and spread around. The disease can lead to yield reductions as a result from defoliation, flower abortion and fruit lesions [48,49]. The damages caused by Pst can be remarkable in nurseries, greenhouses, and fields during warm and humid conditions [50].…”
Section: Pseudomonas Syringae Pv Tomato (Okabe) Young Dye and Wilkiementioning
confidence: 99%